Intake of Lactobacillus paragasseri SBT2055 improves subjective symptoms of common cold during winter season in healthy adults: A randomized, double-blind, placebo-controlled parallel-group comparative study - Kobatake, Eiji; Iwama, Yoshitaka; Arai, Toshinobu; Shioya, Nobuhiko; Kise, Mai; Kabuki, Toshihide (Frontiers in Nutrition, 2022)
Objective: Lactobacillus paragasseri SBT2055 (LG2055) has been reported to show immunostimulating effects. This study aimed to investigate the effects of LG2055 on the subjective symptoms of the physical condition in healthy adults. Materials and Methods: In this randomized, double-blind, placebo-controlled, parallel-group comparative study, Japanese individuals aged 20-64 years were recruited. A total of 200 participants were randomly divided into two groups by an independent controller (LG2055 and placebo groups; 100 participants per group). Drinkable yogurts containing LG2055 or lacking LG2055 (placebo) were used as test samples. The participants ingested one bottle of the test sample once a day for 12 weeks. A daily physical health questionnaire survey (about common cold symptoms) was performed as the primary outcome, and immunological and oxidative stress markers in saliva and serum were evaluated as secondary outcomes. Results: In total, 198 participants completed the scheduled intake of the test samples, and five participants were excluded from the final analysis. Consequently, 193 participants (LG2055 group, n = 97; placebo group, n = 96) in the Per-Protocol Set were included in the efficacy analysis. The cumulative days of each symptom were evaluated, and the LG2055 group showed a significantly higher ratio of “without symptom” in runny nose, plugged nose, sneezing, sore throat, hoarseness, cough, headache, feeling tired, and fever than the placebo group, indicating that the incidence rates of common cold symptoms were lower in the LG2055 group. Additionally, changes in the salivary secretory IgA levels were significantly higher, and the serum derivatives of reactive oxygen metabolites levels were significantly lower in the LG2055 group. Conclusion: Our study revealed that intake of LG2055 decreased common cold symptoms and improved immune parameters in healthy adults. This suggests that LG2055 contributes to the maintenance of physical conditions by improving the host immune system. Clinical Trial Registration: [https://www.umin.ac.jp/ctr/index.htm], identifier [UMIN000045901].